Ameliorative Effect of Grape Seed Proanthocyanidin Extract on Cadmium‐Induced Meiosis Inhibition During Oogenesis in Chicken Embryos. Issue 4 (11th February 2016) - Hou, Fuyin; Xiao, Min; Li, Jian; Cook, Devin W.; Zeng, Weidong; Zhang, Caiqiao; Mi, Yuling
ABSTRACT: Cadmium (Cd) is an environmental endocrine disruptor that has toxic effects on the female reproductive system. Here the ameliorative effect of grape seed proanthocyanidin extract (GSPE) on Cd‐induced meiosis inhibition during oogenesis was explored. As compared with controls, chicken embryos exposed to Cd (3 µg/egg) displayed a changed oocyte morphology, decreased number of meiotic germ cells, and decreased expression of the meiotic marker protein γH2AX. Real time RT‐PCR also revealed a significant down‐regulation in the mRNA expressions of various meiosis‐specific markers ( Stra8, Spo11, Scp3, and Dmc1 ) together with those of Raldh2, a retinoic acid (RA) synthetase, and of the receptors ( RARα and RARβ ). In addition, exposure to Cd increased the production of H2 O2 and malondialdehyde in the ovaries and caused a corresponding reduction in glutathione and superoxide dismutase. Simultaneous supplementation of GSPE (150 µg/egg) markedly alleviated the aforementioned Cd‐induced embryotoxic effects by upregulating meiosis‐related proteins and gene expressions and restoring the antioxidative level. Collectively, the findings provided novel insights into the underlying mechanism of Cd‐induced meiosis inhibition and indicated that GSPE might potentially ameliorate related reproductive disorders. Anat Rec, 299:450–460, 2016. © 2016 Wiley Periodicals, Inc.